Overexpression of cytochrome P450 genes in pyrethroid-resistant Culex quinquefasciatus - Komagata, Osamu; Kasai, Shinji; Tomita, Takashi (Insect biochemistry and molecular biology, 2010)
JPal-per strain of Culex quinquefasciatus exhibits extremely high resistance against pyrethroids in larvae, though the resistance is greatly lower in adults. Increased microsome monooxygenase metabolism is one of the major factors of the larval resistance in this strain. We cloned 46 novel cytochrome P450 cDNAs from JPal-per strain. An oligonucleotide microarray was designed for the novel 46 genes plus 16 previously reported P450 genes along with other non-P450 gene probes. Of these, five P450 genes were upregulated (>2.5-fold) in JPal-per larvae as compared with a susceptible strain. The expression ratios for the highest three among the five P450 genes screened in the microarray analysis, CYP9M10, CYP4H34 and CYP6Z10, were further validated by qPCR as 264-, 8.3-, and 3.9-fold, respectively. In JPal-per, the transcription levels of CYP9M10 and CYP4H34 showed a similar stage-dependent pattern as a high expression level during the larvfrom Ogasawara Islands in Japanal stage dramatically decreases in the adult stage. This larval specific overexpression manner of the two genes was consistent with the characteristic of stage-dependent resistance of JPal-per strain previously reported, suggesting that the two P450s, CYP9M10 and CYP4H34, are involved in pyrethroid detoxification in JPal-per strain.